Dimensões da profissionalização e do trabalho de professores de Química: em foco os projetos pedagógicos - Carvalho, Christina Vargas Miranda e (2020)
The tendency towards a technicist character in the Brazilian Chemistry Licentiate Degree Courses presents an obstacle to the constitution of the professional identity of teachers in training, which ends up reflecting on their professionalism and professionalization, as well as on their professional development. Based on this issue, this thesis investigated whether the pedagogical projects of the Chemistry teacher training courses have the formative dimensions necessary for professionalization and professional development of these teachers. To this end, we proposed an innovative way of organizing Chemistry Licentiate Degree Course curriculum based on Formative Dimensions. Grounded in the field of teacher education critical perspective, we used the conceptions of Pimenta, Nóvoa and Tardif as theoretical assumptions. Our study objects were the pedagogical proposals for Chemistry Licentiate Degree Courses of Minas Gerais state public higher education institutions, specifically, Federal University of Juiz de Fora (UFJF), Federal University of Uberlândia (UFU) and Federal University of Viçosa (UFV) courses. The methodological path comprised a descriptive documentary research outlined by qualitative approach. The results were discussed based on content analysis as proposed by Bardin. The analytic categories were defined a priori and constituted of the Formative Dimensions established by this thesis, which were: (i) basic conceptual and disciplinary dimension; (ii) interdisciplinary and interprofessional dimension; (iii) instrumental, technical and practical dimension; (iv) aesthetic and cultural dimension; (v) ethical and political dimension; (vi) socioemotional dimension; (vii) transversal socio-referential dimension; and (viii) transversal investigative dimension. We understand that teacher training courses with pedagogical proposals structured in accordance with these Formative Dimensions, allow graduates to practice and experience diversified training opportunities that instigate their professionalism in teaching, promote their professional development and provide acquisition and construction of theoretical, practical, investigative, political, social, ethical, aesthetic and cultural knowledge, which are necessary for teaching practice. We identified that the course offered by UFV presents the tendency, historically identified in Brazilian Chemistry Licentiate Degree Courses, to offer teaching training courses with bachelor degree profile, revealing a gap in the constitution of teacher’s professional identity. However, there is a possibility that the original curriculum is not fully followed and that many of the weakness identified may have already been solved by teachers who work on that course. Still, it must be considered that most courses aimed at teacher training have shortcomings and even so, they form excellent professionals. The pedagogical projects of UFJF and UFU courses, despite the need for some adjustments, encompass many aspects of the Formative Dimensions proposed by this thesis, providing the opportunity for these Chemical teachers to build a professional identity. Finally, we infer that the Formative Dimensions proposed by this thesis fulfill their purpose of establishing guiding principles for teacher training and expand Tardif's conceptions about teaching knowledge.